Laboratory-scale bioremediation potential of single and consortia fungal isolates from two natural hydrocarbon seepages in Trinidad, West Indies. Issue 3 (3rd July 2019) - Ramoutar, Sheldon; Mohammed, Azad; Ramsubhag, Adesh
Abstract: A study was conducted to isolate and evaluate the hydrocarbon-degrading potential of indigenous fungi in consortia from natural petroleum seepages in Trinidad. Sixty-seven isolates were obtained from two seepages using medium containing four single hydrocarbon fractions: diesel, naphthalene, pyrene, and asphaltene. The majority of the isolates belonged to the genera Aspergillus (52%) and Fusarium ( 20%), while fewer belonged to the genera Penicillium and Curvularia, and the order Mucorales (2–14%). The isolates were initially screened for degradation of crude oil in BSM broth before the top 16 (4 per hydrocarbon) were evaluated in soil spiked with single hydrocarbons over 28 days. Three consortia comprising the best performing isolates from each hydrocarbon were then evaluated for their bioremediation potential using soil spiked with crude oil and the four hydrocarbons. Consortium 1, comprising of the top degraders ( Aspergillus terreus- SRF-15 (diesel), Fusarium proliferatum- SRF-50 (naphthalene), Fusarium sp-SRF-58, (pyrene) and Aspergillus sp-SRF-67 (asphaltene)), was the most effective with a total petroleum hydrocarbon degradation rate of 92% as compared to the other consortia (64–76%) and the single isolates (10–65%) over a 28-day period. The results of this study show great potential for using indigenous fungi to develop consortia for bioremediation in tropical environments.